Practical Life Skill Activities On The Independence Of 5-6 Year-Old Children In Perigi Primary Kindergarten, - Zuhut Ramdani; Moh. Alwi Ashari; Titin Yulastri Bastiana (STABN RADEN WIJAYA WONOGIRI, 2020)
Independence is ability to complete tasks without assistance, enabling children to develop optimally. This study aims to determine the increase in children’s independence through Montessori practical life skills activities. The study was conducted at Putra Perigi Kindergarten, with 12 class B students as subjects. The research method used was quantitative research and a pre-experimental design with a One Group Pretest-Posttest Design. The instruments used to collect data included validation sheets, observation sheets, and documentation.The results showed that the level of independence of 150 children during the pre-test obtained an averange percentage of 45%, which falls into the category of beginning to develop. After treatment and a post-test, the results showed an increase in the children’s independence abilities, with 27 children scoring an average percentage of 81%, which falls into the category of very well develop. Based on the results of the hypothesis calculation, also using the t-test, the calculated t-value is 21.39 with a t-table value of 2.201. therefore, the calculated t-value (21.39)> t-table(2.201) proves that the results of the hypothesis analysis in this study are that H_a is accepted and H_o is rejected.